Sistema de gestão para biblioteca universitária (SGBU) - Dziekaniak, Cibele Vasconcelos (2003)
This work presents the System of Management for University Library (SGBU) as a methodological suggestion for the management of University Library. This way, the model of proposed system is divided in six subsystems which are: institutional subsystem, management subsystem, operational subsystem, organizational subsystem, human-behavioral subsystem and environmental subsystem. The methodological ways used in this study were: exploratory research; qualitative boarding; three types of technical ways: bibliographical research, research in documents and the case study; the object of study was the University Library; the instruments of data collect used were: non-structured interview, non-systematic observation, natural participation observation, field notes of reflective essence, analysis of home documents, brainstorming and suggestion box . Simultaneously to the development of SBGU, the implementations were conducted in a University Library case study on purpose to validate the proposed model of System of Management, as well to test yours real applicability. Therefore, it was concluded that a System of Management for University Library which has institutional, management, operational, organizational, human-behavioral, environmental questions, constitute itself in a effective instrument of support to the administrative action of library professional.